Utilization of Video Conferencing for Paramedic-to-Physician Consultations in Pre-Hospital Emergency Care: A Comprehensive Review - Aldahmashi, Majed Azmi Ghanem; alhazmi,YsifSaleh A; Alrawili, Rizgallah Farj A; Aldahmashi, Hamoud Hajji A; Alenezi, Mohammed Mrih M; Alanazi, Abdulaziz Basheer Shami; Alhazmi, Sami Jumah Khatam; Alanazi, Mohammed Qaem Essa; Alhazemi, Muteb Batel Nawman; Alanazi, Abdulaziz Moraya Binyah; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> Pre-hospital emergency care is critical for the handling of acute conditions such as stroke, ST-elevation myocardial infarction (STEMI), and trauma, where timely interventions are life-determining. Video conferencing allows real-time paramedic-to-physician consultations, enhancing decision-making and patient outcomes. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim: <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">The aim of this review is to evaluate the application of video conferencing in pre-hospital EMS, in terms of the technological requirements, legal issues, and impact on pre-hospital care and ED preparedness. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> A narrative review of peer-reviewed literature from 2015 to 2025 was undertaken via PubMed, Scopus, and CINAHL. Keywords were "video conferencing," "telemedicine," "paramedic," and condition-specific terms. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Results: <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Video conferencing improves diagnostic accuracy (e.g., 20% for stroke), treatment adherence (15% increase), and patient outcomes (e.g., 25-minute reduction in stroke door-to-needle time). It improves ED readiness by facilitating communication streamlining, resource allocation (30% reduction in STEMI wait times), and triage efficiency. Challenges include rural connectivity issues, training needs, and legal uncertainties. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> Video conferencing transforms EMS because it enhances care provision and ED preparedness but requires robust technology, clear regulations, and training. Connectivity and AI incorporation are aspects to be prioritized for future research.